Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 46838 by peter frank last updated on 01/Nov/18

Answered by MrW3 last updated on 03/Nov/18

(x^2 /a^2 )+(y^2 /b^2 )=1  ((2x)/a^2 )+((2y)/b^2 )y′=0⇒(x/a^2 )+(y/b^2 )y′=0  e^2 =((a^2 −b^2 )/a^2 )    eqn. of circle:  (x−c)^2 +y^2 =r^2   (say)  2(x−c)+2yy′=0⇒(x−c)+yy′=0    contact points: (ea,k) and (ea,−k)  ((e^2 a^2 )/a^2 )+(k^2 /b^2 )=1  e^2 +(k^2 /b^2 )=1  ⇒e^2 b^2 +k^2 =b^2    ...(i)  (ea−c)^2 +k^2 =r^2    ...(ii)  ((ea)/a^2 )+(k/b^2 )m=0  ((eb^2 )/a)+km=0   ...(iii)  ea−c+km=0   ...(iv)    (i)−(ii):  e^2 b^2 −(ea−c)^2 =b^2 −r^2    ...(v)  (iii)−(iv):  ((eb^2 )/a)−ea+c=0  ⇒c=e(a−(b^2 /a))=((e(a^2 −b^2 ))/a)=e^3 a  from (v):  r^2 =b^2 (1−e^2 )+(ea−c)^2 =b^2 (1−e^2 )+((e^2 b^4 )/a^2 )=b^2 [1−((e^2 (a^2 −b^2 )/a^2 )]=b^2 (1−e^4 )=a^2 (1−e^2 )(1−e^4 )=a^2 (1−e^2 −e^4 +e^6 )  ⇒eqn. of circle:  (x−e^3 a)^2 +y^2 =b^2 (1−e^4 )  y^2 +x^2 −2ae^3 x+a^2 e^6 =a^2 (1−e^2 −e^4 +e^6 )  ⇒y^2 +x^2 −2ae^3 x=a^2 (1−e^2 −e^4 )

x2a2+y2b2=12xa2+2yb2y=0xa2+yb2y=0e2=a2b2a2eqn.ofcircle:(xc)2+y2=r2(say)2(xc)+2yy=0(xc)+yy=0contactpoints:(ea,k)and(ea,k)e2a2a2+k2b2=1e2+k2b2=1e2b2+k2=b2...(i)(eac)2+k2=r2...(ii)eaa2+kb2m=0eb2a+km=0...(iii)eac+km=0...(iv)(i)(ii):e2b2(eac)2=b2r2...(v)(iii)(iv):eb2aea+c=0c=e(ab2a)=e(a2b2)a=e3afrom(v):r2=b2(1e2)+(eac)2=b2(1e2)+e2b4a2=b2[1e2(a2b2a2]=b2(1e4)=a2(1e2)(1e4)=a2(1e2e4+e6)eqn.ofcircle:(xe3a)2+y2=b2(1e4)y2+x22ae3x+a2e6=a2(1e2e4+e6)y2+x22ae3x=a2(1e2e4)

Commented by peter frank last updated on 04/Nov/18

thank you mrW_3

thankyoumrW3

Terms of Service

Privacy Policy

Contact: info@tinkutara.com